Liquidity Management and the Performance of the Pharmaceutical Sector in Nigeria - elizabeth OYEWUNMI DUROTOYE; ikpefan OCHEI AILEMEN; oluwatobi DAVID FASHEYITAN (Communications of International Proceedings, 2022)
Majority of pharmaceutical companies in Nigeria have been experiencing revenue losses since 2009 till date  due  to lack of funding for capacity development as well as ineffective working capital management practices. There has been minimal empirical research on this relationship in the Nigerian pharmaceutical companies. This study examined how current ratio affect the profitability in the pharmaceutical industry in Nigeria. The empirical investigation was focused on the liquidity policies and practices of six (6) publicly traded pharmaceutical companies on the Nigerian stock exchange (NSE). The methodology employed in this research is the panel data using fixed effect approach. The fixed effect approach takes into consideration both the dependent and independent variable. The data employed is a panel data of six pharmaceutical companies covering period of 2015-2019. The result shows that overall assets and cash and cash equivalents boost annual earning. Using total assets and cash and cash equivalent in production can help pharmaceutical companies expand. The study recommended that pharmaceutical firms should focus more on asset building since it enhances productivity and less emphasis should be placed on current liability unless in cases where the firm cannot do otherwise.
Keywords: Liquidity management; current ratio; pharmaceutical firms; Working capital